1989
DOI: 10.1007/bf03337777
|View full text |Cite
|
Sign up to set email alerts
|

Exploration-dependent modulation of evoked responses in fascia dentata: Fundamental observations and time course

Abstract: The hippocampal formation is thought to be involved in spatiallearning. A role as a more general, intermediate-term memory store has also been suggested. In this report, we address a moderately persistent change in propagation of excitation through hippocampal circuitry which resulted from exposure of animals to environments in which they were free to move and explore. Rats were prepared for chronic recording of perforant path-evoked dentate granule-cell population responses. A large increase in the synaptic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 41 publications
3
28
1
Order By: Relevance
“…Third, as noted by Sharp et al (1989) during periods of intense locomotor activity such as transitions between environments or, as in the present experiments, treadmill walking, there was a substantial, but transient, decline in the field EPSP amplitude. The proportional reduction of EPSP amplitude during treadmill walking was independent of stimulus intensity over a broad range.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Third, as noted by Sharp et al (1989) during periods of intense locomotor activity such as transitions between environments or, as in the present experiments, treadmill walking, there was a substantial, but transient, decline in the field EPSP amplitude. The proportional reduction of EPSP amplitude during treadmill walking was independent of stimulus intensity over a broad range.…”
Section: Discussionsupporting
confidence: 69%
“…The EPSP reduction recovered immediately upon cessation of the treadmill activity. Sharp et al (1989) reported that this sort of attenuation did not occur in the absence of prior EPSP growth. In the present studies, we found that the attenuation was strictly proportional to the magnitude of the EPSP growth just prior to locomotor activity, rather than to the absolute amplitude of the EPSP itself.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations